The Role of Nutrition in Optimizing Athletic Performance and Recovery: A Literature Review - Rizka Dwi Puspitasari; Aisyah Azzahra Arfajah (Journal of Nutrition and Health Care, 2026)
Nutrition plays a critical role in supporting physical performance and recovery in athletes. Adequate intake of macronutrients and micronutrients, proper hydration, and appropriate supplementation can influence endurance, strength, and speed during training and competition. This study aims to analyze the role of nutrition in optimizing athlete performance and recovery by examining nutritional requirements, hydration strategies, supplement use, and dietary patterns that support muscle regeneration. A literature review approach was employed, analyzing scientific articles, books, and recent research reports on sports nutrition, physical recovery, and supplementation. Data were analyzed descriptively and analytically to identify the relationship between nutrient intake and physical performance indicators, as well as the effectiveness of recovery strategies following athletic activities.mThe findings indicate that balanced consumption of carbohydrates, proteins, healthy fats, vitamins, and minerals enhances energy capacity, accelerates muscle recovery, and reduces fatigue and injury risk. Proper hydration also supports bodily homeostasis and maintains performance during training or competition. Targeted supplementation, when applied appropriately, can further enhance physiological adaptation and muscle tissue regeneration. Overall, systematic nutrition planning and personalized nutrient intake are essential for improving performance and accelerating recovery in athletes. These findings provide practical guidance for coaches, sports nutritionists, and athletes in developing effective nutritional strategies to support athletic achievement and long-term health.